2018
DOI: 10.1149/2.0481805jes
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Electrochromic V2O5Thin Films with Ultrahigh Coloration Efficiency on Graphene Electrodes

Abstract: Flexible multi-color electrochromic V 2 O 5 thin films have been prepared by electrochemical deposition on the double-layer Graphene/PET substrates. The deposited films have a layered structure with nano-crystals in the amorphous matrix, which contributes to an ultrahigh coloration efficiency of ∼555.83 cm 2 C −1 @800 nm and a large transmittance modulation of 68.94% @800 nm. The large interlayer distance of 1.20 nm, good electrolyte penetration, and short lithium ion diffusion distance make some key electroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…While the obtained values are comparable to values previously reported by us for structurally related monolayer-based ECDs, , the values are significantly larger than that reported for the majority of metalorganic-based ECDs, where a value of 750 cm 2 /C is considered exceptional . The η values of our monolayer-based ECDs are drastically larger than that reported for viologen-based ECMs (<301 cm 2 C –1 ) ,, and inorganic metal oxide systems, where the coloration efficiency of ∼556 cm 2 C –1 was referred to as “ultrahigh” in its class. , There was one literature report on the organic-based ECD that demonstrated similarly high values of coloration efficiency (≥1240 cm 2 C –1 ) . In addition, the van der Boom group reported on ECDs based on polypyridine layer-by-layer architectures on the flat ITO glass electrodes that demonstrated a similar ultrahigh CE of 1488 cm 2 /C …”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…While the obtained values are comparable to values previously reported by us for structurally related monolayer-based ECDs, , the values are significantly larger than that reported for the majority of metalorganic-based ECDs, where a value of 750 cm 2 /C is considered exceptional . The η values of our monolayer-based ECDs are drastically larger than that reported for viologen-based ECMs (<301 cm 2 C –1 ) ,, and inorganic metal oxide systems, where the coloration efficiency of ∼556 cm 2 C –1 was referred to as “ultrahigh” in its class. , There was one literature report on the organic-based ECD that demonstrated similarly high values of coloration efficiency (≥1240 cm 2 C –1 ) . In addition, the van der Boom group reported on ECDs based on polypyridine layer-by-layer architectures on the flat ITO glass electrodes that demonstrated a similar ultrahigh CE of 1488 cm 2 /C …”
Section: Resultssupporting
confidence: 77%
“…52 The η values of our monolayer-based ECDs are drastically larger than that reported for viologen-based ECMs (<301 cm 2 C −1 ) 9,53,54 and inorganic metal oxide systems, where the coloration efficiency of ∼556 cm 2 C −1 was referred to as "ultrahigh" in its class. 55,56 There was one literature report on the organic-based ECD that demonstrated similarly high values of coloration efficiency (≥1240 cm 2 C −1 ). 49 In addition, the van der Boom group reported on ECDs based on polypyridine layer-by-layer architectures on the flat ITO glass electrodes that demonstrated a similar ultrahigh CE of 1488 cm 2 /C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Details of the experimental procedure have been reported elsewhere. [ 10 ] After electrodeposition, the absolute ethyl alcohol was used to rinse the loosely bounded particles on the surface of the V 2 O 5 thin films. Finally, the samples were dried at 60 °C for 12 h in air.…”
Section: Methodsmentioning
confidence: 99%
“…[ 17 ] In terms of nanocrystal‐in‐glass V 2 O 5 thin films, we have proposed ex situ Raman spectroscopic analysis to identify a distinct difference of three vibrational modes of OVOVO, VO 3 bending, and VO stretching between colored and bleached states in our previous work. [ 10 ] Although such ex situ Raman spectroscopic characterization of the V 2 O 5 thin films has been widely considered, designing in situ strategy to uncover the dynamically structural transformation of nanocrystal‐in‐glass V 2 O 5 electrode in real‐time during its electrochemical lithium intercalation and deintercalation still needs to be experimentally explored further.…”
Section: Introductionmentioning
confidence: 99%
“…Another example is that the porous structure of WO 3 film is helpful for promoting the electrolyte infiltration and alleviating the expansion of the WO 3 during H + (proton) insertion. 8 It is demonstrated that the EC performance (such as coloration efficiency and optical modulation) in well-ordered material structure exhibits inferior properties, as compared to the amorphous EC materials such as WO 3 , 7,9 V 2 O 5 , 10,11 and NbO x . 12 As stated previously, 12 electrochromic performance of indium tin oxide (ITO)-in-NbO x composites with nanocrystalin-glass is better than the undoped amorphous NbO x .…”
Section: Introductionmentioning
confidence: 99%